Suplementácia zinku, selénu a medi cestou cepco-bachorových peliet a jej vplyv na úroven cellulárnej a humorálnej odpovede u oviec - Bíres, J; Michna, A; Bartko, P; Pistl, J; Juhásová, Z (Veterinarni medicina, 1993)
The objective of the study was to test the effectiveness of Zn, Se and Cu supplementation through reticulum-rumen pellets and its effects on the rate of cellular and humoral reactions in sheep. An experiment included 12 lambing ewes of the Merino breed at the age of two years. Zn-containing pellets were applied via rumen to three lambing ewes at the end of November, Se pellets were applied to other three lambing ewes Cu pellets to other three ewes. Three lambing ewes were control. Blood samples were taken from the v. jugularis from all the investigated ewes before bolus administration, in month 1, 2, 3, 4, 6 and 7 after application. Zn, Se and Cu concentrations in the blood serum were determined by atomic absorption spectrophotometry. Immune reactions were evaluated from the concentrations of serum immunoglobulins (IgC), albumin (ALB), total proteins (TP), from phagocytic activity (PA), phagocytic index (PI), migration-inhibitory test (MIT) and determination of tetrazolium-reductase activity of phagocytes (INT-test). In comparison with the starting values, the highest increase in zincemia (80%) was recorded in the lambing ewes administered zinc boluses as soon as in the 1st month after administration. A significant difference in Zn concentrations between the zinc-pellet group and the control animals was observed in the 1st month after administration (P < 0.01). An increase in Se concentrations in the blood serum was observed in the lambing ewes administered selenium boluses in the 1st month after administration. Se content in the blood serum of the given group of ewes was highest at the end of observation (2.72 +/- 0.29 mumol/l). A statistically significant difference in Se content between the group of selenium-bolus ewes and the control ewes was confirmed at a significance level P < 0.05 in the 1st and 2nd month of the experiment. Cu concentrations in the blood serum in the Cu-bolus ewes increased in the 1st month if compared with the starting values. The highest Cu concentration in the blood serum was recorded in the given group within month 4 to 7 of the experiment (16.53 +/- 2.72, or 21.23 +/- 4.40 mumol/l). There were significant differences in cupremia between the Cu-pellet group of ewes and the control animals (P < 0.05). In comparison with the starting values, the highest increase in TP concentrations were determined in the Cu-pellet ewes in the 4th, 6th, and 7th months. Albuminemia dynamics in the experimental animals and in the control group did not vary significantly.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: imunita; Immunity; měď; bachor; selen; Female; Sheep; Animal Feed; Animals; Copper; ženské pohlaví; Rumen; Zinc; krmivo pro zvířata; zvířata; zinek; ovce; Selenium